Desertos da informação : estiagem, seca e jornalismo científico - Zermiani, Raul Tavela (2016)
This research performs the rhetorical analysis of the Brazilian scientific journalism on drought and drier occurred in southeastern Brazil in 2014. Structurally, the thesis presents a discussion on the relationship between Science, Scientific Communication and Diffusion; summarizes the condition of the printing press in the context of dissemination of science; exposes the theoretical framework and proceeds application of rhetoric in the biggest newspaper in the texts of Brazil that accompanied the theme. As appendices, produces a guide for quick reference of the types of arguments and rhetorical figures.